2020
DOI: 10.1177/1464420720931886
|View full text |Cite
|
Sign up to set email alerts
|

Design and development of a wedge shaped magnetorheological clutch

Abstract: This paper presents a novel drum magnetorheological clutch design having a wedge shaped boundary. The converging film formed due to the direction of motion of the magnetorheological clutch and the inclination of the wedge planes helps to produce the pressure generating mechanism in the magnetorheological grease film. The resistance force developed due to this mechanism in the proposed case exceeds that of the conventional drum clutch. The proposed wedge shaped drum magnetorheological clutch consists of bimetal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Manish Kumar Thakur et al, using simulation techniques and experimental studies, created a new seal for an outer radius that is designed to improve the torque transmission of a magnetorheological clutch, and the transmitted torque was measured and studied for improvement [12]. Anurag Singh et al designed a new drum magnetorheological clutch with a wedge-shaped boundary, and experimental results showed that the proposed wedge-shaped drum magnetorheological clutch generated more torque than the existing drum magnetorheological clutch, thus resulting in better performance [13]. M. D. Christie et al proposed a magnetorheological fluid-based differential (planetary) gear transmission that variably connects motor power to a load attached to the planetary carrier output through a sun gear input [14].…”
Section: Introductionmentioning
confidence: 99%
“…Manish Kumar Thakur et al, using simulation techniques and experimental studies, created a new seal for an outer radius that is designed to improve the torque transmission of a magnetorheological clutch, and the transmitted torque was measured and studied for improvement [12]. Anurag Singh et al designed a new drum magnetorheological clutch with a wedge-shaped boundary, and experimental results showed that the proposed wedge-shaped drum magnetorheological clutch generated more torque than the existing drum magnetorheological clutch, thus resulting in better performance [13]. M. D. Christie et al proposed a magnetorheological fluid-based differential (planetary) gear transmission that variably connects motor power to a load attached to the planetary carrier output through a sun gear input [14].…”
Section: Introductionmentioning
confidence: 99%
“…The iron particles evenly disperse to the carrier fluids in milliseconds after the magnetic field is removed, making it possible to control the MR effect almost in real-time conditions. Because of these characteristics, MR fluids are widely used in various device applications, including MR clutches [2], MR brakes [3], MR dampers [4], and MR mounts [5]. Another 2 of 16 technology for material removal [6,7] and medical devices has also been proposed [8].…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic flux can be generated by a permanent magnet (Bucchi et al, 2014; Rizzo et al, 2015), but is often generated by a magnetic coil for fast response actuators (Fauteux et al, 2010). The shear interface can have various geometries (Nam and Ahn, 2009; Pisetskiy and Kermani, 2020; Singh et al, 2020; Wang et al, 2013) but the two main geometries are the disk type (Bucchi et al, 2017; Pisetskiy and Kermani, 2021; Shafer and Kermani, 2011b) and the drum type (Lebel et al, 2021; Qin et al, 2018; Rossa et al, 2014; Figure 3). Another type is called serpentine, and consists of one large drum where the magnetic flux crosses the same MR fluid gap several times, in a serpentine way (Blake and Gurocak, 2005; Senkal and Gurocak, 2009).…”
Section: Introductionmentioning
confidence: 99%